Glycosphingolipid storage leads to the enhanced degradation of the B cell receptor in Sandhoff disease mice. - te Vruchte, D; Jeans, A; Platt, F; Sillence, D (2010)
Glycosphingolipid storage diseases are a group of inherited metabolic diseases in which glycosphingolipids accumulate due to their impaired lysosomal breakdown. Splenic B cells isolated from NPC1, Sandhoff, GM1-gangliosidosis and Fabry disease mouse models showed large (20- to 30-fold) increases in disease specific glycosphingolipids and up to a 4-fold increase in cholesterol. The magnitude of glycosphingolipid storage was in the order NPC1 > Sandhoff approximately GM1 gangliosidosis > Fabry. Except for Fabry disease, glycosphingolipid storage led to an increase in the lysosomal compartment and altered glycosphingolipid trafficking. In order to investigate the consequences of storage on B cell function, the levels of surface expression of B cell IgM receptor and its associated components were quantitated in Sandhoff B cells, since they are all raft-associated on activation. Both the B cell receptor, CD21 and CD19 had decreased cell surface expression. In contrast, CD40 and MHC II, surface receptors that do not associate with lipid rafts, were unchanged. Using a pulse chase biotinylation procedure, surface B cell receptors on a Sandhoff lymphoblast cell line were found to have a significantly decreased half-life. Increased co-localization of fluorescently conjugated cholera toxin and lysosomes was also observed in Sandhoff B cells. Glycosphingolipid storage leads to the enhanced formation of lysosomal lipid rafts, altered endocytic trafficking and increased degradation of the B cell receptor.